Why medical innovation is valuable: Health, human capital, and the labor market - Nicholas W. Papageorge (Quantitative Economics, 2016)
I develop a dynamic framework to assess the value of pharmaceutical innovation, taking explicit account of how side effects and the labor market affect the demand for medical treatment. In the framework, forward-looking patients do not simply maximize underlying health or longevity. Rather, they choose labor supply and medicine in light of potential side effects in an effort to jointly manage two forms of human capital: their health and their work experience. I use the framework to examine the treatment and employment decisions of human immunodeficiency virus (HIV) positive men before and after a medical break- through known as highly active anti-retroviral treatment. A novelty of this application is my use of data containing both objective health measures along with reports of physical ailments. This allows me to model each HIV drug along two dimensions of quality-effectiveness and side effects. Using the framework, I am able to identify the impact of side effects on demand and show that counterfac- tual innovations that reduce side effects can be very valuable. I also show that when no treatment dominates along both dimensions of drug quality, patients exhibit health-state-dependent cyclicality in their medical treatment decisions, favoring effective treatments despite side effects when in poor health, but switching to less effective drugs with fewer side effects (or avoiding treatment altogether) when their health improves.
Keywords: I10; J24; O31; 330; Innovation; health; human capital; labor; structural models; HIV/AIDS